1998
DOI: 10.1039/a802944j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high salt concentrations on the determination of arsenic and selenium by flow injection hydride generation electrothermal atomic absorption spectrometry

Abstract: In the determination of arsenic and selenium by flow injection hydride generation ETAAS, the presence of up to 20% sodium chloride enhanced the signals for 20 mg l 21 arsenic and selenium by up to 28%. The enhancement was obtained with a variety of gas-liquid separators. A systematic study of the possible causes of the signal enhancement in the determination of selenium was undertaken, from which it was concluded that the effect originated in the processes responsible for the distribution of the hydrogen selen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…In order to improve the situation, a method of automatic introduction of the volatile hydrides into the atomiser should be examined. Nevertheless, it should be emphasised that even the simplest variant of determinations with the manual insertion of the capillary tube results in a relative standard deviation (RSD) in the range of 4.2 % -12.8 % for the concentrations of 2 ng/ml, and 0.1 ng/ml for determinations of the total content of selenium, which is acceptable for this concentration of selenium and comparable with the results reported by other authors [9,21,22].…”
Section: Characterisation Of the Analytical Methodssupporting
confidence: 71%
“…In order to improve the situation, a method of automatic introduction of the volatile hydrides into the atomiser should be examined. Nevertheless, it should be emphasised that even the simplest variant of determinations with the manual insertion of the capillary tube results in a relative standard deviation (RSD) in the range of 4.2 % -12.8 % for the concentrations of 2 ng/ml, and 0.1 ng/ml for determinations of the total content of selenium, which is acceptable for this concentration of selenium and comparable with the results reported by other authors [9,21,22].…”
Section: Characterisation Of the Analytical Methodssupporting
confidence: 71%
“…Matrix effects were determined comparing the slopes of calibration curves using matrix-matched standards with those applying pure solvent standards. Matrix effects >0% may be encountered in flow-injection systems in the presence of salts coeluting with arsenic species and hence reducing the solubility of the corresponding arsine [15]. The LODs of this method for As(III), As(V), MMA and DMA are comparable to those of most other studies or are even lower [1,5,7,[16][17][18].…”
Section: Limit Of Detection Precision and Matrix Effectssupporting
confidence: 59%
“…Arsenic chloride formation is fundamentally free from classical transition metal interferences. Ellis et al 14 studied the effect of NaCl on hydride generation efficiency and concluded that the increased salt concentration had a positive effect on the signal intensity of arsenic and selenium hydrides. Their explanation was based on the 'salting out' effect, to account for an improved gas-liquid separation efficiency.…”
Section: Resultsmentioning
confidence: 99%